The relationship between gender identity and six f0 measures in Polish - Kaźmierski, Kamil (University of Glasgow, 2015)
This paper reports on a study of the relationship between gender identity, as measured by the Bem Sex-Role Inventory (BSRI) and six characteristics of F0 (mean, median, minimum, maximum, range and standard deviation) in semi-spontaneous speech of 24 Polish female speakers. Despite ample evidence suggesting that gender identity exerts an influence on voice quality, notably on pitch, whose main acoustic correlate is F0, the statistical analysis of the data gathered for the present study does not attest to a relationship between the BSRI score and F0 measures. An elaboration of culture-specific tool for measuring gender identity, as well as supplementing acoustic measurements with physiological and articulatory data are suggested as methodological developments needed to verify whether there are links between gender identity and F0 in Polish.
Keywords: fundamental ferquency; gender identity; sociophonetics